Principles of nutritional assessment - Gibson, Rosalind S. (New York : Oxford University Press, 2005)
Comprehensive, authoritative guide to evaluating nutritional status using dietary, anthropometric, biochemical, and clinical methods$1 (Bwidely used in public health and nutrition research.s
1. Nutritional assessment methods -- 2. Dietary assessment -- 3. Anthropometric techniques -- 4. Laboratory measures -- 5. Clinical assessment -- 6. Survey applications.
Includes bibliographical references and index.
In English
Keywords: Nutrition -- Evaluation